BREATH OF CONFIDENCE: STRATEGIES FOR NURSES’ MASTERY IN TRACHEAL INTUBATION AND TRACHEOSTOMY MANAGEMENT - Al-Sayed, Fatima Ahmed Hassan; Al-Ahmadi, Mahmoud Ali Abdel-Rahman; Ibrahim, Aisha Mohamed Mahmoud (Research Journal of Health, Medicine and Nursing, 2024)
In the realm of critical care nursing, effective management of patients requiring ventilator support is a multifaceted challenge. This study explores the complexities faced by critical care nurses in Sudan, where the demand for mechanical ventilation has surged due to increased chronic illness cases and a growing focus on reducing external healthcare costs. Ventilator support entails addressing various physiological conditions, including those that impede optimal ventilator functionality, and attending to issues such as dyspnea and patient-ventilator desynchrony. During the mechanical ventilation process, patients exhibit diverse responses, necessitating careful monitoring and adjustments to achieve therapeutic goals like enhanced oxygenation, improved ventilation, heightened patient comfort, and the prevention of secondary injuries. While certain technical aspects of ventilator management fall within the purview of respiratory care practitioners, nurses play a crucial role in ensuring holistic patient care. They address common symptoms and responses related to mechanical ventilator support. This study aims to enhance the knowledge and practices of nursing staff concerning endotracheal tube and tracheostomy care.